2020
DOI: 10.1128/mbio.01624-20
|View full text |Cite
|
Sign up to set email alerts
|

HbtR, a Heterofunctional Homolog of the Virulence Regulator TcpP, Facilitates the Transition between Symbiotic and Planktonic Lifestyles in Vibrio fischeri

Abstract: The bioluminescent bacterium Vibrio fischeri forms a mutually beneficial symbiosis with the Hawaiian bobtail squid, Euprymna scolopes, in which the bacteria, housed inside a specialized light organ, produce light used by the squid in its nocturnal activities. Upon hatching, E. scolopes juveniles acquire V. fischeri from the seawater through a complex process that requires, among other factors, chemotaxis by the bacteria along a gradient of N-acetylated sugars into the crypts of the light organ, the niche in wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…This observed "fuzziness" of ES114 litR mutant mimics, although it does not fully match, that of the KB2B1 litR mutant (as well as that of the LuxQ-E74K and LuxO-V106G variants) (compare Figure 6A with Figure 3). These data lend support to the hypotheses that (i) LuxQ-E74K and LuxO-V106G impact motility via inhibiting LitR; and (ii) in addition to inhibiting motility, KB2B1 LitR may control the production/activity of factors necessary for formation of compact rings during migration, such as, perhaps, chemotaxis proteins, as was shown for ES114 (Bennett et al, 2020). Further evaluation of the KB2B1 litR mutant revealed that luminescence was delayed and diminished, verifying that it functions in the quorum sensing pathway controlling luminescence as predicted from ES114 (Figure 6D).…”
Section: Litr Negatively Controls Motility In Kb2b1supporting
confidence: 76%
See 1 more Smart Citation
“…This observed "fuzziness" of ES114 litR mutant mimics, although it does not fully match, that of the KB2B1 litR mutant (as well as that of the LuxQ-E74K and LuxO-V106G variants) (compare Figure 6A with Figure 3). These data lend support to the hypotheses that (i) LuxQ-E74K and LuxO-V106G impact motility via inhibiting LitR; and (ii) in addition to inhibiting motility, KB2B1 LitR may control the production/activity of factors necessary for formation of compact rings during migration, such as, perhaps, chemotaxis proteins, as was shown for ES114 (Bennett et al, 2020). Further evaluation of the KB2B1 litR mutant revealed that luminescence was delayed and diminished, verifying that it functions in the quorum sensing pathway controlling luminescence as predicted from ES114 (Figure 6D).…”
Section: Litr Negatively Controls Motility In Kb2b1supporting
confidence: 76%
“…Thus, a defect in migration could be due to any of these parameters. Indeed, we hypothesize that the “fuzzy” appearance of the migration patterns for the litR mutant derivatives of both ES114 and KB2B1 could be due to altered chemotaxis; Bennett et al (2020) recently determined that LitR represses a set of four chemoreceptors in ES114. However, in our work evaluating luminescence, which takes into account growth rate, we found no evidence to support the idea that migration is severely impacted by growth rate, either in the context of wild-type KB2B1 or its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the attraction to 18:2 stems from planktonic survival and the association of linoleic acid with sediment, stemming from high deposits of omega-6 fatty acids from terrestrial plant matter (Torres-Ruiz & Wehr, 2010; Whatley et al, 2014). It would reason that the squid-associated PUFAs (20:4, 20:5, and 22:6) would not increase motility, since symbiotic bacteria downregulate chemotaxis and motility in the crypts of the squid light organ (Bennett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequences for HNL01 and ICP1 were concatenated and visualized as a dot plot using word size 5 in Geneious Prime (2021.1.1) Plasmid and mutant construction Primers used to create the V. fischeri gene deletion and expression plasmids used in this study are listed in Tables S1 and S3, respectively. In-frame deletion of VF_0175 from the V. fischeri genome was performed as previously described (Bennett et al, 2020;Saltikov and Newman, 2003). Briefly, $1kb fragments surrounding VF_0175 were fused via an internal EcoRI site and inserted via BamHI and SacI sites into pSMV3 (Coursolle and Gralnick, 2010), which has kanamycin resistance and sacB cassettes.…”
Section: Hnl01 Genome Annotation and Comparative Analysis With Vibrio...mentioning
confidence: 99%